2020
DOI: 10.1007/s12369-020-00702-4
|View full text |Cite
|
Sign up to set email alerts
|

“Don’t Get Distracted!”: The Role of Social Robots’ Interaction Style on Users’ Cognitive Performance, Acceptance, and Non-Compliant Behavior

Abstract: Social robots are developed to provide companionship and assistance in the daily life of the children, older, and disable people but also have great potential as educational technology by facilitating learning. In these application areas, a social robot can take the role of a coach by training and assisting individuals also in cognitive tasks. Since a robot’s interaction style affects users’ trust and acceptance, customizing its behavior to the proposed tasks could, potentially, have an impact on the users’ pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 62 publications
0
9
1
Order By: Relevance
“…In addition, to our knowledge, no previous study has included an investigation of the influence of the Big Five personality factors on compliance to a robot in HRI and only one very recent one has used the Eysenck Personality Questionnaire Revised-Short (EPQR-S) to investigate personality traits and non-compliant behavior. However, Maggi et al (2020) have found no relation of users' non-compliant behavior to their personality traits. Therefore, across two studies we examined the effects of physical embodiment and humanlikeness of a robot in a situation where a participant was encouraged by a robotic "coach" to continue practicing a reconnaissance detection task.…”
Section: Our Researchmentioning
confidence: 92%
“…In addition, to our knowledge, no previous study has included an investigation of the influence of the Big Five personality factors on compliance to a robot in HRI and only one very recent one has used the Eysenck Personality Questionnaire Revised-Short (EPQR-S) to investigate personality traits and non-compliant behavior. However, Maggi et al (2020) have found no relation of users' non-compliant behavior to their personality traits. Therefore, across two studies we examined the effects of physical embodiment and humanlikeness of a robot in a situation where a participant was encouraged by a robotic "coach" to continue practicing a reconnaissance detection task.…”
Section: Our Researchmentioning
confidence: 92%
“…This test measures pleasure, arousal, and dominance concerned with the social robot [50]. Both questionnaires, UTAUT and SAM, were scored via Five-Likert pictorial scales (range:1-5) [48,57].…”
Section: Assessment Toolsmentioning
confidence: 99%
“…The current study comprises two experiments: evaluating the proposed lip-syncing system, which determines the robot's capacity to be employed in educational scenarios, and investigating the acceptance of the APO, which affects participants' cognitive performance and compliance behaviors during interaction with the robot [48]. In the first experiment, a video of a normal-hearing individual pronouncing a set of words was first given to a group of adults, who were asked to watch, identify, and write the pronounced words.…”
Section: Introductionmentioning
confidence: 99%
“…Socially assistive robots (SAR) are designed to help vulnerable user populations, such as those who are undergoing rehabilitation, therapy, or require lifelong assistance. They can perform a variety of tasks, including reminding users to take medication (Di Napoli et al, 2023), encouraging physical activity (Fasola and Mataric, 2010), providing cognitive training (Maggi et al, 2021), and offering social and emotional support (Rossi et al, 2020). To account for the variability in tasks and users' behaviours, researchers are focusing on the role of the robot's adaptive behaviour.…”
Section: Introductionmentioning
confidence: 99%